The Role of Christian Clerics in Promoting Good Governance and Development in Nigeria: Prophet Amos as a Model - Omosor, Festus Osom (NIU Journal of Humanities; Vol 4 No 3 (2019): KIU Journal of Humanities, Vol. 4 No. 3, September 2019, 2019)
Religion has been part of socio-political movements from the down of human consciousness. Thus, religion is a veritable tool for shaping and stirring of the human society. Therefore, clerics who invariably wield so much influence on adherents occupy key place in nation building. This is evident in both biblical era and the present day Nigeria. Nigeria is one of the most religious countries in the world with Christianity forming about the largest religious group, yet the realities in the socio-political landscape of the nation leave much to be desired. This paper examines the role of Christian clerics in promoting good governance and development in Nigeria in the light of the prophetic engagement of Amos in the eight century Israel. The study adopts the historical, comparative and evaluative approaches. The paper submits that the Christian clerical vocation in Nigeria is not effective in checkmating socio-political actions and the promotion of good governance and development due to partisanship and self-aggrandizement. The paper advocates the prophetic paradigm of the eighth century biblical prophecy which separated clerical vocation from partisan politics in order to function effectively in contributing to good governance and development. Keywords: Christian Clerics, Prophecy, Governance, Development, Model.